THE USE OF CHATGPT AS AN INTERACTIVE MEDIUM TO IMPROVE WRITING SKILLS OF ELEMENTARY TEACHER EDUCATION STUDENTS AT NAHDLATUL ULAMA UNIVERSITY OF SIDOARJO - Achmad Wahyudi; ryan, ryan purnomo; Pratama, Pratama Wirya Atmaja (Journal of English Language Teaching and Islamic Integration, 2025)
This study aims to optimize writing instruction management in the Elementary School Teacher Education (PGSD) program using ChatGPT as an interactive media tool based on artificial intelligence (AI). Writing skills are essential competencies that support literacy development, academic communication, and critical thinking for pre-service teachers. However, many PGSD students still struggle with organizing ideas coherently, using proper sentence structures, and applying correct grammar consistently. ChatGPT, as a generative AI model, offers adaptive and responsive learning interactions, enabling students to receive instant feedback, suggestions for improvement, and idea enrichment. This research employed a true experimental approach with a pre-test post-test control group design, involving PGSD students at Nahdlatul Ulama University of Sidoarjo. The experimental group used ChatGPT in writing instruction, while the control group followed conventional methods. Research instruments included observation, writing tests (pre-test and post-test), student response questionnaires, and interviews with lecturers. The analysis showed that the experimental group experienced a significantly greater improvement in writing skills compared to the control group. The average score of the experimental group increased from 63.5 to 81.2 (a gain of 17.7 points), while the control group only improved from 64.1 to 71.3 (a gain of 7.2 points). Questionnaire results also indicated that students felt ChatGPT helped them generate writing ideas (86%), correct grammar (91%), build confidence (78%), and enhance motivation (84%). These findings demonstrate that integrating ChatGPT into writing instruction is effective in improving academic literacy and learning management among PGSD students.